Effect of Bisphosphonates on Function and Mobility Among Children With Osteogenesis Imperfecta: A Systematic Review. (18th October 2019) - Constantino, Christopher S.; Krzak, Joseph J.; Fial, Alissa V.; Kruger, Karen M.; Rammer, Jacob R.; Radmanovic, Katarina; Smith, Peter A.; Harris, Gerald F.
ABSTRACT: Osteogenesis imperfecta (OI) is a rare genetic connective tissue disorder that results in bone fragility and deformity. Management is multi‐disciplinary. Although pharmacologic intervention with bisphosphonates (BP) is a standard of care for individuals with severe OI, no consensus or reviews were found that focus on the effects of bisphosphonates on function and mobility. PubMed, CINAHL, Cochrane Library, Web of Science, and PEDro databases were searched for eligible articles for this review. Methodological quality was assessed using the Cochrane Collaboration's tool for risk of bias. Twenty‐six studies (801 children) were reviewed and five showed a low risk of bias. Included studies showed significant variability among clinical protocols for administering BP. Randomized controlled trials did not demonstrate a significant improvement in function and mobility with oral BP administration, while non‐randomized open‐label uncontrolled studies demonstrated that oral and intravenous BP administration objectively improved function and mobility. The most common outcome measure used by the studies included in this review was the Bleck score. Effect sizes (d = 0.28 ‐ 4.5) varied among studies. This systematic review also summarized the apparent confounding variables affecting results of previous studies and provided suggestions to improve the quality of future studies.